Yiddish: biography of a language - Shandler, Jeffrey (Oxford University Press USA- OSO, 2020)
Yiddish: Biography of a Language presents the story of the foundational vernacular of Ashkenazi Jews, from its origins to the present, spoken around the world. This book examines the uses of Yiddish and values invested in it to trace the dynamic interrelation of the language, its speakers, and their cultures.